(untitled) (Progressive Agriculture, 2013)
Improved fish burger was developed from pangus fish (Pangasius sutchi) by using different kinds of food additives (25% mashed potato, 2% NaCl, 2% oil, 2% spices such as onion, ginger, garlic, green chili, hot spices and 0.6% sugar). Proximate composition and sensory, chemical and microbiological changes of pangus fish burger were determined to evaluate the shelf life and storage stability kept at room (28ºC) and refrigeration (5ºC) temperature. It was observed that, the moisture, pH and protein contents in pangus burger were decreased than that of fish mince. On the other hand, lipid and ash contents were higher. Among the variable levels of mashed potato level, 25% mashed potato level showed the best sensory performance and was recommended for the commercial production. At room temperature, the sensory attributes deceased significantly (P<0.05) throughout the storage period. On the other hand, at refrigerated temperature (5°C) the product was more stable. The TVB-N value increased progressively throughout the storage period (P<0.05) at both room (28°C) and refrigerated (5°C) temperature. The microbial load was also increased significantly (P<0.05) at both temperatures but the growth pattern was slower at refrigeration temperature. After considering all the results, it was concluded that, the shelf life of pangus fish burger was very short, in fact not more than 24 hours at 28ºC. On the other hand at 5ºC pangus fish burger may remain in good condition up to 72 hours. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16867 Progress. Agric. 20(1 & 2): 153 162, 2009